An interoperable and standardized protocol for reporting systematic conservation planning projects - Martin Jung; Vanessa M. Adams; Diogo Alagador; Jorge G. Álvarez‐Romero; Miguel B. Araujo; Anni Arponen; Maria Beger; Jutta Beher; Silvia B. Carvalho; Sylvaine Giakoumi; Jeffrey O. Hanson; Virgilio Hermoso; et al. (Conservation Science and Practice, 2025)
Abstract Systematic conservation planning (SCP) is an operational and scientific framework that assists in deciding where, how, and when to implement conservation intervention. Studies using SCP approaches have proliferated due to their immediate relevance for applied conservation. For example, they can help identify cost‐effective opportunities for expanding areas under conservation management to achieve high‐level policy goals such as those of the Global Biodiversity Framework. Yet SCP can be conducted in various ways, and results can vary depending on problem formulation, parameterizations, contexts, and prioritization approaches. There is a need to facilitate comparison of SCP studies to understand key criteria and assumptions made in the planning process. Here, we propose a standardized reporting protocol for SCP that is readily applicable across study aims, realms, and spatial scales. The new Overview and Design Protocol for Systematic Conservation Planning (ODPSCP) describes the key steps from the design to the computational stages of SCP. It enables researchers, scientific editors, and decision‐ and policymakers to assess the scope and comprehensiveness of SCP exercises. To facilitate uptake and ease of reporting, the protocol is openly available through an interactive web interface and which can be further enhanced following methodological advancements in conservation planning. We encourage the conservation community to adopt the reporting protocol to promote transparency and reproducibility, standardized reporting as well as facilitate peer review and independent evaluation.